2003
DOI: 10.1038/sj.bjc.6600707
|View full text |Cite
|
Sign up to set email alerts
|

Degree of tumour vascularity correlates with drug accumulation and tumour response upon TNF-α-based isolated hepatic perfusion

Abstract: Isolated hepatic perfusion (IHP) with melphalan with or without tumour necrosis factor alpha (TNF-a) is currently performed in clinical trials in patients with hepatic metastases. Previous studies led to the hypothesis that the use of TNF-a in isolated limb perfusion causes specific destruction of tumour endothelial cells and thereby induces an increased permeability of tumour vasculature. However, whether TNF-a contributes to the therapeutic efficacy in IHP still remains unclear. In an in vivo rat liver metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Although low-dose TNF has a favorable effect on angiogenesis, higher doses cause destruction of newly formed blood vessels [38]. Concordantly, TNF induces a dose-dependent reduction of tumor blood flow [39,40], and the degree of tumor vascularization directly correlates with tumor response to TNF-based treatment both in animal and human models [34,[41][42][43].…”
Section: Tnf and Tumor Vasculaturementioning
confidence: 99%
“…Although low-dose TNF has a favorable effect on angiogenesis, higher doses cause destruction of newly formed blood vessels [38]. Concordantly, TNF induces a dose-dependent reduction of tumor blood flow [39,40], and the degree of tumor vascularization directly correlates with tumor response to TNF-based treatment both in animal and human models [34,[41][42][43].…”
Section: Tnf and Tumor Vasculaturementioning
confidence: 99%
“…TNF-α is directly cytotoxic for tumor cells [2] and has indirect toxicity by affecting endothelial cells and tumor vascularization [3][4][5]. By combining TNF-α and a cytostatic drug like melphalan, a synergistic effect on the tumor activity can be obtained, because of an immediate TNF-mediated tumorselective enhanced drug uptake of the cytostatic agent [6,7], dependent on the vascularity of the tumor [8], followed by a tumor-selective eradication of the tumor-associated vasculature [9]. In the clinical setting the combination of TNF-α, interferon-γ and melphalan in isolated limb perfusion has lead to a limb salvage rate of 90% in isolated limb perfusion for irresectable melanomas and sarcomas [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies IL-2 has been shown to have powerful anti-tumor effects and has been used for the treatment of melanoma and renal cell carcinoma in the clinic (Overwijk et al, 2000). TNF-α is a multifunctional cytokine that possesses anti-tumor activity including destruction of the tumor endothelial cells, increasing vascular permeability (van Etten et al, 2003), inhibition of tumor angiogenesis mediated by generation of angiostatin (Mauceri et al, 2002). TNF-α can not only inhibit the growth of tumor cells but also kill tumor cells directly through cytolysis.…”
Section: Discussionmentioning
confidence: 99%